Niklas Luhmann’s Radical Communication Approach and Its Implications for Research on Organizational Communication - Cooren, François; Seidl, David (Academy of Management Review, 2020)
In this review essay, we explore how Luhmann’s radical communication approach, which conceptualizes communication without recourse to human beings’ intentions, can reorient existing research on organizational communication. We show how Luhmann’s perspective puts decisions back into organizational communication studies, how it changes our perspective on organizational continuity and on organizational boundaries, and how it redirects our understanding of human agency in organizations. We also discuss three areas in which Luhmann’s theory could draw inspiration from other research on organizational communication. Keywords: autopoiesis, communication, Niklas Luhmann, organization studies, systems theory.